Modeling of Benzene with Ethylene Alkylation - Khlebnikova E. S. Elena Sergeevna; Dolganova I. O. Irena Olegovna; Ivashkina E. N. Elena Nikolaevna; Koshkin S. A. Stanislav Aleksandrovich (Chemical Kinetics, 2016)
Title screen